The Relationship Between Fatigue and Quality of Life in Pediatric Leukemia Patients Undergoing Chemotherapy - Amalia Ayuturrahmi; Ririn Muthia Zukhra; Arneliwati Arneliwati (Journal of Education Technology Information Social Sciences and Health, 2025)
Children with leukemia undergo treatment in the form of chemotherapy. The side effects of chemotherapy can lead to fatigue, which in turn may affect their daily functioning and overall quality of life. This study aims to analyze the relationship between fatigue and the quality of life in pediatric leukemia patients undergoing chemotherapy at Arifin Achmad General Hospital, Pekanbaru. The research design used is a descriptive correlational study with a cross-sectional approach. The study sample consisted of 41 children with leukemia (26 boys and 15 girls) aged 5–12 years, selected through purposive sampling at the Seruni Unit. The study utilized the PedsQL™ MFS (Multidimensional Fatigue Scale) and PedsQL™ 4.0 (Generic Core Scales) questionnaires. The results showed that the average fatigue score among the children was 44.0, indicating a moderate level of fatigue, with the majority experiencing cognitive function impairment (mean score of 16.5). The average quality of life score was 61.1, with most children experiencing physical function impairment (mean score of 22.5), and 29 respondents (70.7%) were found to have impaired quality of life. The Spearman Rank test revealed a significant relationship between fatigue and quality of life in children with leukemia undergoing chemotherapy. The findings of this study are expected to serve as a reference for improving the quality of life of children with cancer by minimizing the side effects of their treatment, thereby maintaining their overall well-being.